Developing a localized resilience assessment framework for historical districts: A case study of Yazd, Iran - Saeedeh Moayedfar; Hossein Mohebbi; Najmeh Mozaffaree Pour; Ayyoob Sharifi (PLoS ONE, 2025)
Growing natural and man-made disasters necessitate enhanced resilience in urban historical districts, vital for cultural heritage and tourism. This study aims to develop a localized assessment framework tailored to the unique characteristics of Yazd, Iran, a UNESCO World Heritage site known for its ancient architecture and cultural significance. By adapting and downscaling indicators from established DROP and BRIC models, we evaluated resilience across seven key dimensions and 17 criteria. Using advanced multi-criteria decision-making methods, including Delphi, Fuzzy DEMATEL, Fuzzy ANP, and VIKOR, we prioritized and ranked the historical districts based on their resilience scores. The results revealed that the social dimension and housing infrastructure are the most crucial factors for resilience. Environmental and institutional dimensions, while important, were found to be less critical in comparison. The VIKOR analysis identified specific districts with lower adaptability, requiring targeted interventions. These findings provide valuable information for policymakers and urban planners, offering a robust framework for enhancing urban historical district resilience. This study provides a context-specific approach to resilience assessment, emphasizing the need for tailored strategies to preserve and strengthen the resilience of culturally significant urban areas.